HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN SE-GUGUS IV KECAMATAN LIMAPULUH KOTA PEKANBARU - Nora Utami; Hendri Marhadi; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is students in learning which will affect the study result. The purpose of the research was correlation between students motivation with student learning results in mathematics of IV grade SDN cluster IV in Limapuluh district Pekanbaru city. This research method was correlational. The technique sampling of using probability sampling is cluster sampling. The collection data of using questionare method and techique documentation of the value MID second semester of academic year 2015/2016. The technique analysis use is the technique of product moment. Test analysis prerequisite in the from of normality test and linearity test. The technique analysis and prerequisite test analysis of using program SPSS 20. The research result showed that there is a positive correlation between learning motivation with learning mathematics result of IV grade students of SDN cluster IV in Limapuluh district Pekanbaru city, obtained of rxy 0,303 with a low level of correlation as well the motivation to learn contributes learning result of 9,2 %. The result of hypothesis testing of using correlation test, there significant correlation between learning motivation with learning mathematics result of IV grade students of SDN cluster IV in Limapuluh district Pekanbaru city, obtained r hitung (0,303) > r tabel (0,233) and significant value of 0,010 which shall mean less 0,05 (0,010 < 0,05). Base on these result, the hypothesis in this research ho rejected and ha accepted means there is a positive and significant correlation between learning motivation with learning mathematics result of IV grade student of SDN cluster IV in Limapuluh district Pekanbaru city 2015/2016 school year are accepted of proven.Keyword: The Learning Motivation, Learning Mathematic Result